Comparison of characteristics and immune responses between paired human nasal and bronchial epithelial organoids - Lu Zhu; Wenhao Yang; Jiaxin Luo; Danli Lu; Yanan Hu; Rui Zhang; Yan Li; Li Qiu; Zelian Chen; Lina Chen; Hanmin Liu (Cell & Bioscience)
Abstract Background The nasal epithelium, as part of a continuous and integrated airway epithelium, provides a more accessible sample source than the bronchial epithelium. However, the similarities and differences in gene expression patterns and immune responses between these two sites have not been extensively studied. Results Four lines of matched nasal and bronchial airway epithelial cells obtained from the four patients were embedded in Matrigel and cultured in thechemically defined medium to generate patient-derived nasal organoids (NO) and bronchial organoids (BO). Histologic examination of nasal organoid tissue revealed high similarity and a reduced ciliary beat frequency compared to bronchial organoid tissue. Whole exome sequencing revealed that over 99% of single nucleotides were shared between the NO and matched BO and there was a 95% overlap in their RNA transcriptomes. RNA sequencing analysis of differentially expressed genes indicated a significant reduction in the immune response in NO. RSV infection revealed more productive replication in NO, with a downregulated immune pathway identified by RNA sequencing analysis and upregulated levels of pro-inflammatory cytokines in culture supernatants in NO compared to BO. Conclusions NO and BO serve as robust in vitro models, faithfully recapitulating the biological characteristics of upper respiratory epithelial cells. The different regions of respiratory epithelial cells exhibit distinct immune responses, underscoring their complementary roles in exploring airway immune mechanisms and disease pathophysiology.